An analytical method of estimating diffusion coefficients of gases in liquids from pressure decay tests. Issue 1 (9th October 2018) - Yang, Zehao; Bryant, Steven; Dong, Mingzhe; Hassanzadeh, Hassan
Abstract : We present an exact solution of quasi‐equilibrium model, based on pressure decay technique, to measure diffusion coefficient. The results of the quasi‐equilibrium model are compared with the traditional equilibrium model and it was found that the latter is only a special case of former one. We provide new approximate solution to estimate diffusion coefficient that is more convenient to use, compared with the previously reported approaches. It also reveals that our solution is capable of taking into account greater portion of the collected pressure decay test data and is more accurate. Based on the developed solution, estimation approaches, including linear method and exponential method, are presented and applied to analyze synthetic and experimental pressure‐decay data. The quasi‐equilibrium model is also compared with the traditional equilibrium model. The results reveal that analysis of the test data using equilibrium model may introduce large error in estimation of diffusion coefficient. © 2018 American Institute of Chemical Engineers AIChE J, 65: 434–445, 2019